Evaluation of an Adaptive Game that Uses EEG Measures Validated during the Design Process as Inputs to a Biocybernetic Loop - Ewing, Kate C.; Fairclough, Stephen H.; Gilleade, Kiel (Frontiers in Human Neuroscience, 2016)
Biocybernetic adaptation is a form of physiological computing whereby real-time data streaming from the brain and body is used by a negative control loop to adapt the user interface. This paper describes the development of an adaptive game system that is designed to maximize player engagement by utilizing changes in real-time EEG to adjust the level of game demand. The research consists of four main stages (1) the development of a conceptual framework upon which to model the interaction between person and system, (2) the validation of the psychophysiological inference underpinning the loop, (3) the construction of a working prototype, and (4) an evaluation of the adaptive game. Two studies are reported; the first demonstrates the sensitivity of EEG power in the (frontal) theta and (parietal) alpha bands to changing levels of game demand. These variables were then reformulated within the working biocybernetic control loop designed to maximize player engagement. The second study evaluated the performance of an adaptive game of Tetris with respect to system behavior and user experience. Important issues for the design and evaluation of closed-loop interfaces are discussed.